(untitled) (Research, Society and Development, 2021)
Objective: To describe the profile of nursing students at a private institution and to highlight their knowledge about the Bladder Catheter. Methodology: a descriptive study, with a quantitative approach, carried out in the period of the second semester of 2017, aimed at data collection, of nursing students from all periods of the night shift through a structured and closed questionnaire. The research was carried out in a private higher education institution in Niterói, Rio de Janeiro, Brazil. Results: The profile of the nursing student who enters a private university, is an audience of young adults who are already inserted in the labor market and seek university, motivated by the rise of their careers, as well as improved salaries. The knowledge of academics becomes homogeneous when compared in general, but when separated from health professionals, they have a greater number of correct answers, suggesting that professional activity can be a facilitator for assimilation of content. Conclusion: It is concluded that the sociodemographic profile of nursing students does not interfere in the process of learning and assimilation of content. In view of these results, it suggests other research related to the hindering of the learning process and the student’s knowledge about Urinary Tract Infection, as well as a comparison of the academic profile and the knowledge of the same about the theme in public universities as a comparative and improvement objective in the quality of education and training of nursing professionals.